Role Playing Learning Models in Short Story Materials in SMA 1 Sidrap - Andi Sadapotto; abd kahar; Syamsu T; Nadirah Nadirah; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
The study's goals are to 1) determine how guessing games help second-class students improve their English-speaking abilities. 2. To understand the challenges second-class students are having with improving their English-speaking abilities. To illustrate the evolution and challenges encountered in using guessing games, the researcher used descriptive methods and purposive sampling. The results showed that 6 (20%) of the 30 pupils were classed as having very good grades, 12 (40%) as having good grades, 9 (30%) as having average grades, 3 (10%) as having low grades, and none as having very poor grades. It demonstrated that they were very interested in integrating the teaching and learning of English language using a guessing game technique